Effectiveness of Online Learning When Implementing Collaborative Online Learning In Flipped Classroom - Van Thien, NGO (Technium Social Sciences Journal, 2021)
The COVID 19 pandemic has forced schools, Universities to deliver courses in online learning environments. Finding an effective online learning model is crucial for online teachers to design, develop, and deliver an online course. This research has been conducted to analyze the online learning activities through using collaborative online learning in the flipped classroom for the students at the college level. Data have been gathered through an online questionnaire and it was sent to 300 first-year students in the department of electronic and electrical engineering attending physics courses at Cao Thang Technical College. Cronbach’s Alpha is applied to evaluate the reliability and internal consistency of the associated factors. The exploratory factor analysis is performed to extract the variables and measure the factor loading in this study. Nine factors have been found to evaluate the effectiveness of collaborative online learning with flipped classroom, including goal and learning outcome (GLO), assessment strategy (AS), learning task (LT), course content (CC), learning resource materials (LRM), collaborative online learning (COL), types of interactions (ToI), types of presence (ToP), problem-solving task in post-class (PST-PC). The relationship between the dependent variable and independent variables is determined by using the linear regression model. The results show that nine independent variables were used in the study viz. GLO, AS, LT, CC, LRM, COL, ToI, ToP, and PST-PC positively impact students’ satisfaction and further students’ satisfaction positively impact the effectiveness of online learning (EOL).